Maternal HIV is associated with reduced growth in the first year of life among infants in the Eastern region of Ghana: the Research to Improve Infant Nutrition and Growth (RIING) Project. Issue 4 (20th August 2012) - Lartey, Anna; Marquis, Grace S.; Mazur, Robert; Perez‐Escamilla, Rafael; Brakohiapa, Lucy; Ampofo, William; Sellen, Daniel; Adu‐Afarwuah, Seth
Abstract Children of HIV‐infected mothers experience poor growth, but not much is understood about the extent to which such children are affected. The Research to Improve Infant Nutrition and Growth (RIING) Project used a longitudinal study design to investigate the association between maternal HIV status and growth among Ghanaian infants in the first year of life. Pregnant women in their third trimester were enrolled into three groups: HIV‐negative (HIV‐N, n = 185), HIV‐positive (HIV‐P, n = 190) and HIV‐unknown (HIV‐U, n = 177). Socioeconomic data were collected. Infant weight and length were measured at birth and every month until 12 months of age. Weight‐for‐age (WAZ), weight‐for‐length (WLZ) and length‐for‐age (LAZ) z‐scores were compared using analysis of covariance. Infant HIV status was not known as most mothers declined to test their children's status at 12 months. Adjusted mean WAZ and LAZ at birth were significantly higher for infants of HIV‐N compared with infants of HIV‐P mothers. The prevalence of underweight at 12 months in the HIV‐N, HIV‐P and HIV‐U were 6.6%, 27.5% and 9.9% (P < 0.05), respectively. By 12 months, the prevalence of stunting was significantly different (HIV‐N = 6.0%, HIV‐P = 26.5% and HIV‐U = 5.0%, P < 0.05). The adjusted mean ± SE LAZ (0.57 ± 0.11 vs. −0.95 ± 0.12; P < 0.005) was significantly greater for infants of HIV‐N mothers than infants of HIV‐P mothers. Maternal HIV is associated with reduce infant growth in weight and length throughout the first year of life. Children of HIV‐P mothers living in socioeconomically deprived communities need special support to mitigate any negative effect on growth performance.